Alternariol-induced cytotoxicity in Caco-2 cells. Protective effect of the phenolic fraction from virgin olive oil. (January 2015) - Chiesi, C.; Fernandez-Blanco, C.; Cossignani, L.; Font, G.; Ruiz, M.J.
Abstract: The extra virgin olive oil (EVOO) has been associated to antioxidant effects. The mycotoxin alternariol (AOH) can contaminate olives. The aims of this work were to determine the cytotoxic effects and reactive oxygen species (ROS) produced by AOH, tyrosol and oleuropein (two polyphenols of olive oil) and a real EVOO extract in Caco-2 cells. The MTT assay and the ROS production by the H2 -DCFDA probe were used. Results demonstrated that AOH reduces cellular proliferation depending on concentration, whereas tyrosol and oleuropein did not (12.5–100 μM). The combination of AOH + oleuropein (50 μM) increased cell proliferation (24%) whereas, AOH + tyrosol decreased (47%) it. Besides, AOH increased ROS generation depending on time and concentration. Oleuropein + AOH decreased ROS production. However, 25 μM of tyrosol increased 1.2-fold the ROS production. Respect to the EVOO extract, cytoprotective effect (151%) was evidenced, even with the combination EVOO extract + AOH (15%–55% respect to cells exposed to AOH alone). ROS generation was significantly reduced compared to ROS generation produced by 25 μM of AOH alone. The phenolic antioxidant of EVOO decreases cytotoxicity and ROS production in Caco-2 cells exposed to AOH. Thus, polyphenols of EVOO could contribute to diminish the toxicological risk that mycotoxins can produce to humans. Highlights: AOH reduces cellular proliferation depending on the concentration. AOH produced ROS generation in a time a concentration dependent manner. The oleuropein, tyrosol and EVOO extracts were not cytotoxic to Caco-2 cells. Combinations of AOH + polyphenols or AOH + EVOO reduce cytotoxicity and ROS generation. Caco-2 cells exposed to AOH were protected by polyphenols and EVOO extract.